Antibiotic Sensitivity, ESBL production and Prevalence of blaSHV and blaOXA genes in Escherichia coli from Urinary Tract Infection (Bangladesh Journal of Microbiology, 2016)
Ninety five Escherichia coli isolates from diagnosed urinary tract infections were examined for antibiotic resistance, ESBL production and the presence of two ESBL producing genes blaSHV and blaOXA. It was observed that the prevalence of UTI was most in ages between 19 to 45 years. All the isolates were resistant against different antibiotics including the third generation cephalosporins. Resistance against ciprofloxacin, the frequently prescribed drug was 82%. Only meropenem and nitrofurantoin showed greater sensitivity towards the isolates showing 13 % and 33 % resistance respectively. The resistances were 90, 86, 82 , 79 , 78, 76, 75, 75, 74, 73, 72, 68, 33 and for amoxicillin, nalidixic acid, ciprofloxacin, cephalexin, ceftriaxone, cefixime, amoxiclav, ceftazidime, netilmicin, aztreonam, gentamicin, amikacin, nitrofurantoin and meropenem respectively. Thirtyone isolates were randomly selected for detection of ESBL Production by double disc diffusion synergy test. Twenty one isolates (67.74%) were positive in ESBL production. PCR experiments were carried out using the 21 ESBL positive E. coli isolates to examine the presence of two ESBL genes namely blaSHV and blaOXA. All (100%) of the 21 isolates showed the presence of blaOXA gene, whereas 8 (38%) isolates among the 21 showed the presence of blaSHV gene.Bangladesh J Microbiol, Volume 30, Number 1-2,June-Dec 2013, pp 65-70